2020
DOI: 10.3174/ajnr.a6817
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Brain MRI Pattern in 2 Patients with COVID-19 Acute Respiratory Distress Syndrome

Abstract: We report the cases of 2 patients hospitalized in our intensive care unit with confirmed coronavirus disease 2019 infection in whom brain MR imaging showed an unusual DWI pattern with nodular and ring-shaped lesions involving the periventricular and deep white matter. We discuss the possible reasons for these findings and their relationship to the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Both our cases depicted lesions showing ring-shaped diffusion restriction, previously described in two cases (Toledano-Massiah et al 2020 ). This feature is reminiscent of cytotoxic edema at the leading edge of demyelination.…”
Section: Discussionsupporting
confidence: 73%
“…Both our cases depicted lesions showing ring-shaped diffusion restriction, previously described in two cases (Toledano-Massiah et al 2020 ). This feature is reminiscent of cytotoxic edema at the leading edge of demyelination.…”
Section: Discussionsupporting
confidence: 73%
“…Several mechanisms for the SARS-CoV-2-related neurological complications are being considered: (a) a direct viral invasion (haematogenic or retrograde axonal by olfactory mucosa to olfactory bulbs) to the brain, which can lead to intracellular virus accumulation in endothelial cells (endothelitis with thrombotic microangiopathy) [ 17 , 18 , 19 , 20 , 21 ], neurons, Reference [ 22 ] glial cells, macrophages; (b) an indirect process resulting from hypercoagulability-related [ 23 ]; (c) an exaggerated cytokine [ 20 ]/immune-mediated response to viral infection causing damage to blood vessel wall or cells in the brain [ 24 ] with (d) ischemia, hypoxic, References [ 17 , 24 ] and (e) treatment complications [ 25 ] or (f) a combination of some or all of them [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also showed radiological–pathological correlates of these microlesions, which included red blood cell extravasation, ischemia, deficiency, but not loss of axons and myelin, and microglial response [ 19 ]. Our patients did not have lesions in the corpus callosum, which may be a sign of a bad clinical picture and a worse clinical outcome [ 16 , 19 ]. Significant consequences and pathological changes after infection remained on all organs, especially on the lung parenchyma [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Toledano-Massiah et al showed two patients with a severe SARS-CoV-2 infection who had an MRI of the brain with unusual nodular and annular lesions periventricularly, and within the white matter, it was hyperintensive on the FLAIR sequence. The corpus callosum was also affected [ 16 ]. Flores et al showed extensive pontine and midbrain hemorrhage with penetration into the 3rd and 4th ventricles [ 17 ].…”
Section: Introductionmentioning
confidence: 99%